MANTRA ORANG JAWA: TINJAUAN SINGKAT - Sulistiati, Sulistiati (Balai Bahasa Jawa Timur, 2007)
Indonesian is known to be very religious society. It can be seen through the good growth of literature works both oral and written, such as